Development of Education in the North-Eastern States A Study in National Perspective - Pathak, K.N.; Tomar, J.S. (JOURNAL OF INDIAN EDUCATION, 2015)
The development in education sector in the North Eastern (NE) states of India in the last 67 years since independence needs to be reviewed. Government of India has been providing financial support to North Eastern States through various schemes. However, in spite of that, the pace of development under different sub sectors of education has been uneven. Four NE States namely Tripura, Meghalaya, Arunachal Pradesh and Sikkim have made significant (>25%) improvement in raising the literacy rate. An analysis of Pupil - Teacher Ratio (PTR) in different NE states over the given 20 years period reveals that while the PTR has changed adversely in case of Manipur and Meghalaya, it has improved significantly in Assam, Mizoram and Tripura. Teachers’ training scenario at primary stage is very pathetic in Nagaland, Manipur, Arunachal Pradesh and Mizoram. In only three of eight NE States (i.e., Assam, Sikkim and Tripura) more than 50 % primary school teachers are trained. The scenario in case of Middle/Senior Basic Schools is more or less the same as that of the primary stage. Keeping in view the trend of achievements in terms of GER for girls at upper primary level, the States of Nagaland, Tripura and Sikkim would have to make concerted efforts for success of Sarva Shiksha Abhiyan(SSA), particularly through the focus on upper primary level. An encouraging trend is observed in the expansion of colleges in the North Eastern States. However, the States of Mizoram and Nagaland were still not having a single engineering college till 2008-09. Over two decades’ period, the number of medical colleges in the NE region grew up to 18. However, the State of Mizoram and Nagaland still remained deprived in term of medical education also. In order to reduce the regional disparity and for mainstreaming of the entire North Eastern region, emphasis should be laid on strengthening the institutions as well as quality of education at every stage of education i.e., from Primary to University level.